The Portrait of Translanguaging Process in EFL Classroom Context - Syakila Amelia Octora; Yustika Nur Fajriah; Eva Devi Sofyawati (Ma'soem University, 2026)
This study investigates translanguaging practices employed by an English as a Foreign Language (EFL) teacher in an Indonesian elementary school classroom. The study aims to identify the types of translanguaging used by the teacher and to examine the pedagogical functions of these practices in supporting students’ comprehension, participation, and engagement. A qualitative descriptive research design was adopted, involving classroom observations and a semi-structured interview with one EFL teacher as the primary data sources. The collected data were analyzed thematically to capture recurring patterns of translanguaging use in classroom interaction. The findings suggest that the teacher employed translanguaging through language alternation, insertion, and pronunciation scaffolding to explain vocabulary, give instructions, and model sentence structures. These practices functioned to enhance students’ understanding, increase confidence, and maintain classroom engagement. The study indicates that translanguaging serves as a purposeful pedagogical approach in elementary EFL classrooms, allowing teachers to utilize students’ full linguistic repertoires as valuable learning resources.